Caesarean Myomectomy is No Longer a Dreaded Job: a Case Control Study in Multiple Specialized Centre (Faridpur Medical College Journal, 2013)
Removal of uterine myoma during caesarean section (CS) is not commonly done due to fear of severe haemorrhage which may lead to hysterectomy. Contradicting the previous belief many studies have been showing that myomectomy during caesarean section is a safe procedure without significant increase of risk. The objective of this study is to analyze the safety and clinical outcome of caesarean myomectomy. This is a prospective study carried out in different hospitals of Faridpur district, Bangladesh from 01.01.10 up to 31.12.12. Total 16 (study group) patients had undergone caesarean myomectomy. Operation time, peroperative blood loss, post operative complications and length of hospital staying was compared with that of 32 women (control group) with caesarean section alone. The result shows that peroperative blood loss was average 350±100 ml in study group which is 50 ml more than control group. Operation time was 20 minutes more and length of hospital staying was 1 day more than control group. There was no post partum haemorrhage, no hysterectomy was done at the time of CS and there was no maternal or perinatal mortality. So, caesarean myomectomy is safe and convenient to patient and cost effective without increasing any extra risk. DOI: http://dx.doi.org/10.3329/fmcj.v8i1.16889 Faridpur Med. Coll. J. 2013;8(1): 07-10